Elderlys experiences 2001 - Tornstam, Lars (Uppsala University, 2005)
In 1995 a cross-sectional study of the Swedish population between the ages of 20 and 85 was carried out. In this study, three dimensions of gerotranscendence were approximated and operationalized in three measures: cosmic transcendence, coherence and need for solitude. The general purpose of the 2001 study was to obtain a better understanding of the gerotranscendence patterns when the unlimited age span 65+ is studied in detail.
As in the previous 1995 study, a series of questions/statements were framed in accordance with dimensions of gerotranscendence. Statements measuring the cosmic transcendence included: 'I feel connected with the entire universe', 'I feel that I am part of everything alive', 'I can feel a strong presence of people who are elsewhere', 'Sometimes I feel like I live in the past and present simultaneously', and 'I feel a strong connection with earlier generations'. Coherence was measured by the respondent's attitude to following statements: 'My life feels chaotic and disrupted' and 'The life I have lived has coherence and meaning'. Statements measuring solitude included: 'I like to be myself better than being with others', 'I like meetings with new people', and 'Being at peace and philosophizing by myself is important for my well-being'.
The respondents were also asked if their view on life and existence had changed compared to when they were 50 years old. Respondents were also asked to read a list of common diseases and mark the diseases they suffered from. In the same vein, the respondents were asked if they, during the past two years, had experienced something they regarded as a life crises. Furthermore the respondents were asked how often they: a) participated in activities outside the home (organizational activities, church, cinema, theatre, etc.), b) receive visitors at home (friends, neighbors, children, other relatives), c) themselves visit friends,neighbors, children or other relatives. Response alternatives were: daily, weekly, monthly, every six months, less often.

Purpose:

The general purpose of the 2001 study was to obtain a better understanding of the gerotranscendence patterns when the unlimited age span 65+ is studied in detail

The response rate declined with age from 76 percent in the lowest age category to 53 percent in the highest.

År 1995 genomfördes en tvärsnittsstudie av den svenska befolkningen i åldrarna mellan 20 och 85. I studien studerades och mättes tre dimensioner av gerotranscendens; kosmisk transcendens, sammanhang, och behovet av att vara ensam. Det övergripande syftet med studien var att få en bättre förståelse för de gerotranscendentala mönsterna när man studerar åldrarna 65 år och äldre i detalj. Precis som vid studien som gjordes 1995 ställdes frågor och påståenden i enlighet med de olika dimensionerna. Påståenden som mätte den kosmiska transcendensen var exempelvis: "Jag känner samhörighet med hela universum" "Jag känner att jag är en del av allt levande" "Jag kan känna en stark närvaro av personer som inte är med oss längre" "Ibland känns det som att jag lever i det förflutna och i nutid simultant" "Jag känner en stark koppling till tidigare generationer". Sammanhang mättes genom den svarandes attityder till följande påståenden: "Mitt liv känns kaotiskt och splittrat" "Det liv jag har levt har sammanhang och mening". Påståenden som mätte behov av ensamhet var: "Jag tycker mer om att vara ensam än att vara med andra" "Jag gillar möten med nya människor" "Att vara tillfreds och att filosofera ensam är viktigt för mitt välbefinnande". Man frågande även de svarande huruvida deras syn på livet och existens hade förändrats jämfört med när de var 50 år. De svarande tillfrågandes även att läsa från en lista med olika sjukdomar och markera vilka de led av. Samtidigt frågade man om de svarande hade upplevt något som de uppfattade som en livskris under de senaste två åren. Man frågade även hur ofta de; a) deltog i aktiviteter utanför hemmet (organiserade aktiviteter, kyrkaktviteter, bio, teater). b) fick besök hemma (vänner, grannar, barn, andra anhöriga) c) om de själva beskökte vänner, grannar, barn eller andra anhöriga. Svarsalternativen var; dagligen, veckovis, månadsvis, varje halvår, mindre ofta.

Syfte:

Det övergripande syftet med studien var att få en bättre förståelse för de gerotranscendentala mönsterna när man studerar åldrarna 65 år och äldre i detalj

Svarsfrekvensen minskade i förhållande till ålder, 76% svar i den yngsta åldersgruppen och 53% i den äldsta.
Äldres upplevelser 2001
Keywords: Aged; Äldre; ageing; åldrande; health; hälsa; quality of life; livskvalitet; religious beliefs; religiös tro; General health and well-being; Allmän hälsa och välbefinnande; Elderly; Äldre; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Sociology; Sociologi